Biodiesel Production Innovation Based on Jatropha Curcas and Soybean Oil - Mayowa, Jadesola (International Journal Papier Advance and Scientific Review, 2023)
The study evaluated the potential of Jatropha curcas and soybean oil as feedstocks for biodiesel production and compared the performance of the biodiesels produced. The biodiesels were characterized and their performance was tested in terms of density, viscosity, engine efficiency, power output, and emissions. The results showed that both biodiesels had similar properties and performance compared to conventional diesel fuel, making them suitable alternatives. However, further research and optimization may be required to improve the properties of the biodiesels and ensure their sustainability as feedstocks for biodiesel production. The study provides valuable information for the development of sustainable and eco-friendly energy solutions based on Jatropha curcas and soybean oil as feedstocks for biodiesel production.